On angel mountain - John, Brian (Newport : Greencroft Books, 2013)
Martha Morgan becomes the mistress of the Plas Ingli estate. Though she loves her husband David dearly, she is desperately lonely in a strange house, and her quick wit and cutting humour make her as many enemies as friends. There are mysteries surrounding the great fire that devastated the estate but Martha's questions about it remain unanswered.
Keywords: Wales -- Social life and customs -- 18th century -- Fiction; Historical fiction